Protection of personnel in peace operations : the role of the "safety convention" against the background of general international law - Engdahl, Ola (International humanitarian law series, 2007)
The 1994 Convention on the Safety of United Nations and Associated Personnel was the first multilateral convention to deal specifically with the protection of personnel engaged in peace operations. Effective protection for specific challenges surrounding such operations needs to be addressed. This study looks at some of these challenges.